Brentuximab vedotin in relapsed/refractory Hodgkin lymphoma post-autologous transplant: meta-analysis versus historical data. (May 2015) - Bonthapally, Vijayveer; Wu, Eric; Macalalad, Alexander; Yang, Hongbo; Shonukan, Oluwatoyin; Liu, Yi; Chi, Andy; Huebner, Dirk
Abstract Objective: This meta-analysis evaluated the antitumor activity of brentuximab vedotin versus historical values in patients with relapsed/refractory Hodgkin lymphoma post-autologous stem cell transplantation (ASCT). Methods: A systematic literature review identified studies (1993–February 2013) reporting complete remission (CR) rates in patients with relapsed/refractory Hodgkin lymphoma post-ASCT. Publications reporting CR rates, identified through interrogation of multiple electronic databases and manual searches (with search terms used to capture 'relapsed', 'refractory', 'HL', and 'ASCT'), were included if they reported: ≥20 relapsed/refractory Hodgkin lymphoma patients, where ≥80% were aged ≥12 years and ≥50% had failed prior ASCT. Overall CR rate was determined using a random-effect model, and compared with that reported for brentuximab vedotin in a pivotal phase 2 trial (SG035-0003). Main outcome measures: Across 17 evaluable studies of historical or experimental agents (n = 812), the estimated overall CR rate was 11.1% (95% confidence interval [CI] 7.0, 17.6; range, 0–38.5%) versus 33.3% (95% CI 25.3, 43.9) for brentuximab vedotin (p < 0.0001). In sensitivity analyses, the estimated overall CR rates for historical/experimental agents were 13.6% (95% CI 8.7, 21.4) when only HL trials that reported a CR rate of >0% were included (13 studies; n = 696; p = 0.0009 vs. brentuximab vedotin), and 9.0% (95% CI 4.9, 16.6) when only HL trials were included where CR definition was reported and was measured using the same criteria as in the SG035-0003 study (12 studies; n = 562; p = 0.0001 vs. brentuximab vedotin). Conclusions: Indirect comparisons against a heterogeneous historical sample population naturally limit our ability to draw comparisons, yet the results from this quantitative meta-analysis suggest that the antitumor activity of brentuximab vedotin may exceed that of other therapies used to treat patients with relapsed/refractory Hodgkin lymphoma post-ASCT.